A proposed conceptual framework of programmer's creativity - Amin, A. (Institute of Electrical and Electronics Engineers Inc., 2015)
Research on software engineering was extensive in the last few decades. However, creativity research in software engineering, particularly in different phases of software development, is scarce. Consequently, through extensive literature review and two theories (Componential Theory of Creativity and Theory of Planned Behavior (TPB)) this paper proposes a theoretical framework. The framework theoretically establishes the nature of the impact of three individual factors, namely personality traits, knowledge collection behavior and creativity intention; and one contextual factor, namely software engineering occupational stress, on programmers' creativity. The study will initiate the academic pursuit of understanding creativity in software engineering phases, other than requirement engineering. At the same time, it is aimed to guide the researchers and practitioners to better understand creativity of programmer and to take appropriate measures to enhance her creativity. Â© 2015 IEEE.